Research and Current Issues in Management Accounting (Book). - Haka, Susan F.; Brief, Richard P. (The Accounting Review, 1987)
Abstract Reviews the book "Research and Current Issues in Management Accounting," edited by Michael Bromwich and Anthony G. Hopwood.